The Teacher’s Role in Supporting the ZPD in Students’ English Oral Communication Skills based on the PYP Language Scope and Sequence of Grade EY 3A: A Case Study - Agustina Imelda Kurniasari; Agus Santoso (Polyglot, 2016)
With many international schools implementing bilingual systems in their teaching learning activities, different students who come from different family backgrounds may apply bilingual communication, both at school and at home. For the classroom teacher, one approach to support students’ oral communication skills is through supporting the Zone of Proximal Development (ZPD). In order to make the ZPD happen in the classroom, particularly in the students’ speaking skills, the classroom teacher needs to apply some strategies. The research was descriptive qualitative and the tools used to collect data in the study were in the form of observations, interviews and field notes. The results of the research indicate there are six strategies that the classroom teacher used to support the ZPD. Besides that, there were five aspects that the classroom teacher did to support the students’ oral communication skills and based on the PYP Language Scope and Sequence, the students demonstrated various common trends in their oral communication skills.  BAHASA INDONESIA ABSTRAK: Dengan banyaknya sekolah Internasional yang menerapkan sistem dwibahasa dalam aktivitas belajar mengajar, peserta didik yang berasal dari latar belakang keluarga yang berbeda berkomunikasi menggunakan dua bahasa, baik di sekolah maupun di rumah. Bagi guru kelas, pendekatan yang bisa digunakan untuk mendukung keterampilan berkomunikasi lisan siswa adalah dengan mendukung Zone of Proximal Development (ZPD). Agar ZPD dapat berjalan di kelas, terutama di keterampilan berbicara siswa, guru kelas perlu menerapkan beberapa strategi. Penelitian ini adalah deskriptif kualitatif dan alat yang digunakan untuk mengumpulkan data dalam penelitian ini dalam bentuk observasi, wawancara dan catatan lapangan. Hasil penelitian mengindikasikan ada enam strategi yang  diterapkan guru kelas untuk mendukung Zone of Proximal Development. Di samping itu, ada lima aspek yang dilakukan guru kelas untuk mendukung keterampilan berkomunikasi lisan siswa dan berdasar PYP Language Scope and Sequence, siswa menunjukkan berbagai macam tren yang muncul pada umumnya.